Expression Patterns of Ezrin and AJAP1 and Clinical Significance in Breast Cancer - Xu, Cong; Wang, Feng; Hao, Li; Liu, Jing; Shan, Benjie; Lv, Shuhua; Han, Xinghua; Pan, Yueyin; Niu, Yun (Frontiers in Oncology, 2022)
Ezrin and Adherent junctions associated protein 1(AJAP1) are structural proteins which are involved in numerous human malignancies. However, little is known about the relationship between them in breast cancer. This study was set out to investigate the relationship between them and to further explore the mechanism of AJAP1 mediating cytoskeleton in the breast cancer progression. Ezrin and AJAP1 expression were detected in 377 samples of breast cancer by immunohistochemistry and different expression patterns between AJAP1 and Ezrin with clinicopathological parameters were analyzed. Besides, univariate and multivariate cox model were used to evaluate the prognostic potential of them. Enzyme-linked immunosorbent assay, western blot, qRT-PCR and Phalloidine staining of F-actin were used to explore the relationship and the mechanism between AJAP1 and Ezrin in cytoskeleton arrangement.377 cases of breast cancer results showed that AJAP1 expression was negatively related with histological grade, lymph node involvement and could be an independent prognosis marker of breast cancer. AJAP1 expression tended to be higher in Ezrin-negative expression case. Patients with AJAP1negative and Ezrinpositive expression had a worse prognosis(p<0.0001) and shorter DFS (p=0.015). More importantly, AJAP1-depletion increased cell ability of F-actin formation through promoting Ezrin expression. AJAP1 depletion might mediate breast cancer malignancy potential through promoting Ezrin expression and cytoskeleton formation.